Ḥifẓ al-badan : Risālaʾī Fārsī dar bihdāsht wa tandurustī - Rāzī, Fakhr al-Dīn (Miras Maktoob, ISBN: 9789004365452., 2019)
Fakhr al-Dīn Rāzī (d. 606/1210) was a prominent theologian, interpreter of the Qurʾān, philosopher, and arguably the most important critic of Avicenna (d. 428/1037). He was born in 543/1149 in Rayy, where he studied theology, philosophy and law under different masters, including his father who was a preacher. Having completed his studies, he started a wandering life which took him to different cities and courts in Transoxania and Khwārazm, where he had a number of famous disputes with local scholars. After a brief return to Rayy he finally settled in Herat where he spent the rest of his life, a wealthy and respected scholar with many followers. His works are many, mainly in philosophy and theology, besides his famous commentary on the Qurʾān called Mafātīḥ al-ghayb . Rāzī received a basic medical training during a stopover in Sarakhs 580/1184. The present work is a compendium on preventive medicine and stands in a long tradition.